أنماط القافية في ديوان أحدَ عشر كوكباً لمحمود درويش (Journal of Hama University, 2024)
This research deals with rhyme patterns in modern poetry through the Diwan of Eleven Planets by the Palestinian poet Mahmoud Darwish (1941_ 2008). It seeks to monitor it on several levels and from different perpectives. It talks about rhyme from the syllable point of view and the multiplicity of its syllables. It also deals with the divisions of rhyme according to what was brought by modern poetics, which allowed the multiplicity and diversity of rhymes, talking many forms. This research also monitors the presence of rhyme in terms of its release and restriction. Then, it presents approximate statistics for all this patterns in the studied blog, employing the descriptive upholstery with its stylistic tools, trying to discern its semantic dimensions. The research reached a number of results , the most prominent of which was the clear interest in the rhythmic aspect in the Darwish‘s text through the diversification rhyme patterns that took several forms on each of the studied levels.